Introduction to Brownian Motion in Class XII Senior High School 5 Bengkulu City - Nur Ainayah; Nur Elisa; Iwan Setiawan; Dedy Hamdani (Asosiasi Profesi Multimedia Indonesia, 2022)
Brownian motion is the random motion of nanoparticles in the fluid. The concept of Brownian motion is one of the abstract concepts of physics. Thus, it is difficult to learn. Most schools also don't teach Brownian motion in depth in high school. Including the Senior High School 5 Bengkulu City. In fact, there are a lot of Brown motion applications. For this reason, the introduction of Brownian motion in easy-to-understand language needs to be taught to students. The method used in this research is the method of preparation, implementation, and evaluation. From this research, it can be seen that students are very enthusiastic about listening and answering every question that is asked. There is also a very active participation. The competitive spirit of students is also visible. So, it can be concluded that, no matter how difficult and abstract Brown's motion is, if it is taught in simple language, students are also able to understand it well.